A clinical guidance tool to improve the care of children hospitalized with severe pneumonia in Lusaka, Zambia. Issue 1 (December 2016) - Sutcliffe, Catherine; Thea, Donald; Seidenberg, Philip; Chipeta, James; Mwyanayanda, Lawrence; Somwe, Somwe; Duncan, Julie; Mwale, Magdalene; Mulindwa, Justin; Mwenechenya, Musaku; Izadnegahdar, Rasa; Moss, William
Abstract Background Pneumonia is the leading infectious cause of death among children, with approximately half of deaths attributable to pneumonia occurring in limited health resource settings of sub-Saharan Africa. Clinical guidance tools and checklists have been used to improve health outcomes and standardize care. This study was conducted to evaluate the impact of a clinical guidance tool designed to improve outcomes for children hospitalized with severe pneumonia in Zambia. Methods This study was conducted at University Teaching Hospital in Lusaka, Zambia from October 10, 2011 to March 21, 2014 among children 1 month to 5 years of age with severe pneumonia. In March 2013, a clinical guidance tool was implemented to standardize and improve care. In-hospital mortality pre-and post-implementation was compared. Results Four hundred forty-three children were enrolled in the pre-intervention period and 250 in the post-intervention period. Overall, 18.2 % of children died during hospitalization, with 44 % of deaths occurring within the first 24 h after admission. Mortality was associated with HIV infection status, pneumonia severity, and weight-for-height z-score. Despite improving and standardizing the care received, the clinical guidance tool did not significantly reduce mortality (relative risk: 0.89; 95 % CI: 0.65, 1.23). The tool appeared to be more effective among HIV-exposed but uninfected children and children younger than 6 months of age. Conclusions Simple tools are needed to ensure that children hospitalized with pneumonia receive the best possible care in accordance with recommended guidelines. The clinical guidance tool was well-accepted and easy to use and succeeded in standardizing and improving care. Further research is needed to determine if similar interventions can improve treatment outcomes and should be implemented on a larger scale.